Quantitation of Microorganisms in Sputum - Monroe, P. W. (1969)
A method of quantitating microbial cultures of homogenized sputum has been devised. Possible application of this method to the problem of determining the etiologic agent of lower-respiratory-tract infections has been studied to determine its usefulness as a guide in the management of these infections. Specimens were liquefied by using an equal volume of 2% N-acetyl-L-cysteine. The liquefied sputum suspension was serially diluted to 10(-1), 10(-3), 10(-5), and 10(-7). These dilutions were plated on appropriate media by using an 0.01-ml calibrated loop; they were incubated and examined by standard diagnostic methods. Quantitation of fresh sputum from patients with pneumonia prior to antimicrobial therapy revealed that probable pathogens were present in populations of 10(7) organisms/ml or greater. Normal oropharyngeal flora did not occur in these numbers before therapy. Comparison of microbial counts on fresh and aged sputum showed that it is necessary to use only fresh specimens, since multiplication or death alters both quantitative and qualitative findings. Proper collection and quantitative culturing of homogenized sputum provided information more directly applicable to patient management than did qualitative routine methods. Not only was the recognition of the probable pathogenic organism in pneumonia patients improved, but serial quantitative cultures were particularly useful in recognizing the emergence of superinfections and in evaluating the efficacy of antimicrobial therapy.